If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33 = 0 + 3y Remove the zero: 33 = 3y Solving 33 = 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 33 + -3y = 3y + -3y Combine like terms: 3y + -3y = 0 33 + -3y = 0 Add '-33' to each side of the equation. 33 + -33 + -3y = 0 + -33 Combine like terms: 33 + -33 = 0 0 + -3y = 0 + -33 -3y = 0 + -33 Combine like terms: 0 + -33 = -33 -3y = -33 Divide each side by '-3'. y = 11 Simplifying y = 11
| 3y-2y=8x | | y=3/5+9 | | y=2.5x-2 | | 21/p+1=8 | | a^2-2a+8=0 | | 15+(-4x-18)=9 | | 5n-7=3n-9 | | a/-6+8=12 | | 1-k=27 | | c/4=8 | | d/-2+5=7 | | 16-(9b+3)=4 | | 2(x-2)=16-3x | | -7x+y=-4 | | (2s+4)(2s-4)= | | 7x^2-5=2 | | x/4+10=34 | | 6x-2=-4x+7 | | -9=-20+a | | 17=2x-9 | | 4(x-2)+5x=10 | | 45/450 | | 31=3-4x | | 1+2x-3-4x-5=6 | | 3x/1=2x | | 5*10/4 | | 2(x+4)+5x=50 | | 5n+8=3n | | logs(4x-18)-logs(x-6)=1 | | 3.8=p/3-7.2 | | y/4=5+1 | | 6(x+3)=18 |